Asymptomatic Urinary Abnormalities Among Unselected Adults in a Rural Community in Bauchi, Northeast Nigeria - Abdu Alhaji; Ibrahim M. Maigari; Hamisu Abdulrasheed; Umar Murtala; Binta A. Lasan; Sambo B. Zailani (International Journal of Medicine and Health Development)
Background: Renal diseases have been increasing globally. Chronic kidney disease is a noncommunicable, progressive disease associated with significant morbidity and mortality. Both early detection and treatment could help to prevent the progression of chronic kidney disease. Objective: To assess the prevalence of asymptomatic urine abnormalities in unselected adult rural dwellers. Materials and Methods: This is a screening program of otherwise healthy volunteers at Rijiyar Malam—a rural community in Bauchi State, Nigeria. With the aid of a questionnaire the demographic data were captured; blood pressure, height, weight, and random blood sugar were determined in all respondents who had consented. A urine sample was collected for simple urinalysis and sediment microscopy. Results: A total of 237 subjects were screened, out of which 54.1% were males and 49.1% were females. Proteinuria, hematuria, leucocyturia, and crystalluria were present in 26.5%, 8.8%, 62.2%, and 70.5%, respectively. Combined hematuria and proteinuria were seen in 1.6% of the subjects. Hypertension was seen in 41.8% of the subjects. Among the hypertensives, 12% were aware of their hypertensive status and were on treatment, while 16% were aware of their hypertensive status but never took medications. The mean body mass index (BMI) of the subjects was 21.6 ± 3.6 kg/m2 and only 2.5% were obese. Hyperglycemia was seen in 2.5% of the subjects, including two subjects who were known to have type 2 diabetes mellitus on oral hypoglycemic agents. Conclusion: The prevalence of asymptomatic urinary abnormalities is high in the study population. Further tests are required to confirm the diagnosis of renal diseases in these subjects.